THE EFFECTIVENESS OF SKIMMING AND SCANNING TECHNIQUES IN IMPROVING STUDENTS' READING ABILITY: An Experimental Study in the 2nd Grade Student of UPI Laboratory High School - Andrian Permadi, - (2008)
This research was aimed to find out the effectiveness of skimming and scanning techniques in improving students' reading ability. This study adopted quasi experimental method which was conducted in SMA Laboratorium (Percontohan) UPI for a month. Pre test, treatment and post test served as the research design in this study. In this case, the second grade students in class XI-IPA 1 and XI-IPS 2 became the sample of this research. Reading test were used as the research instrument. The data were analyzed through SPSS 15.0 and interpreted in descriptive way. The result of this study indicated that the means of post test score in experimental group was significantly higher than the control group. In other words, the use of skimming and scanning techniques was effective in improving students reading ability. The research finding was expected to give good contribution to the EFL methodology, Enhance students and teacher knowledge related to reading skills and develop students and teachers creativity in the teaching learning process of reading